Dynamics of O2 and pCO2 in a Southeast Asia seagrass meadow: Metabolic rates and carbon sink capacity - Chou, Wen-Chen; Fan, Lan-Feng; Hung, Chin-Chang; Shih, Yung-Yen; Huang, Wei-Jen; Lui, Hon-Kit; Chen, Tzong-Yueh (Frontiers in Marine Science, 2023)
Dissolved oxygen (DO) and partial pressure of CO2 (pCO2) were measured at half-hourly intervals from June 29 to September 9, 2019, in a seagrass meadow in the Southeast Asia archipelagos region. The open water mass balance of the O2 approach was used to calculate metabolic rates (i.e., gross primary production (GPP), community respiration (CR), and net community production (NCP). The calculations show that GPP and CR rates in the seagrass meadow of Dongsha Island were approximately 2.5 times higher than the global means (GPP, 507 ± 173 vs. 225 ± 11 mmol O2 m-2 d-1; CR, 497 ± 171 vs. 188 ± 10 mmol O2 m-2 d-1), while NCP was similar to the global mean (8 ± 61 vs. 27 ± 6 mmol O2 m-2 d-1), suggesting that seagrass meadows with high GPP may not necessarily hold high potential for carbon sequestration. The current data set also reveal that NCP tended to increase with GPP only at lower GPP levels, while NCP did not increase with GPP anymore at higher GPP levels. Moreover, the autotrophic/heterotrophic status did not correspond well to the sink/source behavior of CO2, suggesting that organic carbon metabolism could not be the only dominant factor in determining the sink/source status in a typical seagrass meadow underlain by carbonate sediments, which was further supported by the observed decrease in the trend of pCO2 with a relatively stable NCP level over the study period. These results demonstrate that the metabolism and the relationship between NCP and pCO2 in the seagrass meadows of Dongsha Island may deviate greatly from the global mean condition. To obtain a better assessment of the global potential of seagrass meadows as a nature-based solution for carbon sequestration, more regional-specific studies are still needed in the key regions, such as Indonesia and the Pacific archipelagos, that support extensive seagrass meadows but have not been charted.